New records of Dipsocoromorpha, Cimicomorpha and Pentatomomorpha (Hemiptera: Heteroptera) from Argentina - Dellapé, Pablo Matías; Carpintero, Diego Leonardo; Melo, María Cecilia (Zootaxa, 2010)
Twenty species of Heteroptera belonging to seven families are recorded for the first time for Argentina: Ceratocombidae (1 sp.), Reduviidae (1 sp.), Miridae (4 sp.), Nabidae (5 sp.), Largidae (2 sp.), Rhyparochromidae (4 sp.), Berytidae (1 sp.), Colobathristidae (1 sp.) and Pachygronthidae (1 sp.). The following genera represent new records from Argentina: Astemmoplitus, Bathycles, Tenuicoris, Pseudopamera (Rhyparochromidae), Diascopoea (Colobathristidae). A new synonym in the family Largidae is established: Largus umbrosus Distant is considered a junior synonym of Largus trochanterus Signoret.